CHPG's role in regulating apoptosis in heat-stressed microglia through endoplasmic reticulum stress: A new perspective☆ - Yan-xuan He; Zhi-qiang Zhang; Xin-xin Zheng; Fan Huang; Guoxin He; Xi-chong Yu; An-cong Xu (IBRO Neuroscience Reports)
Objective: This study aims to explore the influence of microglia-mediated endoplasmic reticulum (ER) stress on cell apoptosis during heat stroke. Understanding this is important as it may help develop new therapies for heat-induced cellular damage and protect glial cells and brain health. Methods: BV-2 cells were used as a cell model for this study. The negative control group was kept at 37°C throughout the experiment. Cells in the experimental group were pretreated with 1 mM CHPG (a selective mGluR5 agonist) for 0.5 hours, followed by heat shock (HS) for 0.5 hours at 40°C and then further cultivation at 37°C for 12 hours. The positive control cells underwent same condition except for drug pretreatment. Several assays were used including CCK8 assay for cell viability, flow cytometry for cell apoptosis index, immunofluorescence for the expression of GRP78, CHOP, and Caspase-12, as well as Western blotting for detecting the protein expression level of GRP78, CHOP, and Caspase-12. Results: Heat shock induced a significant release of endoplasmic reticulum-related proteins and increased the expression levels of GRP78, CHOP, and Caspase-12 in BV-2 cells. CHPG was found to inhibit endoplasmic reticulum stress and cell apoptosis. Conclusion: CHPG may primarily participate in heat shock by mediating endoplasmic reticulum stress and affecting microglia apoptosis.